Histopathological spectrum of chronic skin ulcers in a tertiary care hospital - Feroz, Imza; Wani, Abdul Haseeb; Nazir, Mir Wajahat Un; Lone, Mohammad Iqbal; Parry, Arshed Hussain (International Journal of Clinical Trials, 2019)
Background: The skin is the largest organ of the body, comprising of epidermis, dermis and hypodermis. Thus, a wide range of diseases can develop from the skin ranging from infectious diseases to malignancy, some of which may present as non-healing ulcers. Skin biopsy forms the fundamental basis for differentiation of similar looking lesions, thus helping the pathologists to make a definitive diagnosis and more so to the clinician for better management of patients. The objective was to study the histopathological spectrum of chronic non healing ulcers of skin for proper management and treatment. Methods: This was a hospital-based study which was conducted in SKIMS, Soura, a tertiary care hospital of Kashmir valley for a period of 1 year extending from January 2018 to December 2018. All the patients who presented with the complaint of non-healing ulcer for more than 4 to 6 weeks were subjected to skin biopsy and histopathological examination. Results: A total of 260 biopsies were examined. Out of 260 patients 146 were males and 114 were females. Ninety out of 260 cases (34.61%) and 170 (65.39%) were diagnosed as malignant and benign ulcers respectively. Diabetic ulcer was the second most common cause of non-healing ulcers followed by bacterial infections and tuberculosis. Squamous cell carcinoma was the most common neoplastic pathology. Conclusions: It was concluded from the study that non-healing skin ulcers can be encountered at any age in daily medical practice.